(untitled) (Theatrum historiae, 2019)
When the Borghese family’s ascent to power in the court of Rome began, the domain of the Sandovals within the court of Madrid was already well-established. Through analysis of the correspondence of Nuncio Antonio Caetani, this article underscores how the papal representative promoted himself as a principal interlocutor between these two groups of power. He had to serve the Apostolic See and to satisfy the Spanish ministers and expectations of the nobility, thus increasing the honour of his noble family. A perspective on the relations between Rome and Madrid at the beginning of the seventeenth century will be examined, by focusing on a myriad of recommendations, favours, rewards, and benefices as recompense for gratitude and friendship. The approach purports to deepen the practice of the early modern diplomacy, by considering Caetani’s networks and his perceptions as a privileged observer of court life.